2016
DOI: 10.1002/jrs.5005
|View full text |Cite
|
Sign up to set email alerts
|

High resolution stimulated Raman spectroscopy from collisionally populated states after optical pumping: the 3ν2←2ν2and ν2+2ν45←2ν45Qbranches of12C2H2and the 3ν2←2ν2Qbranch of12C2D2.

Abstract: In this work, we demonstrate the combined use of a pump‐probe Raman–Raman technique and the naturally occurring process of vibration‐to‐vibration (V–V) collisional relaxation to populate and obtain high‐resolution Raman spectra of vibrationally excited states that cannot be easily accessed by other means. First, a stimulated Raman pump stage is used to promote population to a vi = 1 excited state. This is followed by a time interval whose length is chosen so that, at the working pressure, significant V–V colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…They used a pump‐probe Raman‐Raman technique, and the naturally occurring process of vibration‐to‐vibration collisional relaxation to populate to obtain high‐resolution Raman spectra of vibrationally excited states that cannot be easily accessed by other means . In a closely‐related paper first published, these same authors reported high resolution SRS from collisionally populated states after optical pumping: the 3ν2←2ν2 and ν2+2ν4+ν5←2ν4+ν5 Q branches of 12 C 2 H 2 and the 3ν2←2ν2 Q branch of 12 C 2 D 2 …”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…They used a pump‐probe Raman‐Raman technique, and the naturally occurring process of vibration‐to‐vibration collisional relaxation to populate to obtain high‐resolution Raman spectra of vibrationally excited states that cannot be easily accessed by other means . In a closely‐related paper first published, these same authors reported high resolution SRS from collisionally populated states after optical pumping: the 3ν2←2ν2 and ν2+2ν4+ν5←2ν4+ν5 Q branches of 12 C 2 H 2 and the 3ν2←2ν2 Q branch of 12 C 2 D 2 …”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…Spectroscopy methods based on stimulated two-photon transitions, such as two-photon absorption, stimulated emission probing, and stimulated Raman spectroscopy, allow accessing energy states in which typical single photon excitations are forbidden under spectroscopic selection rules [1][2][3]. Stimulated two-photon transition can be used to measure spectral features at sub-Doppler resolution, without the need for cooling or molecular jets [4].…”
Section: Introductionmentioning
confidence: 99%
“…The first results of this study, concerning 12 C 2 H 2 and 12 C 2 D 2 , have already been published. [1] This article presents the results obtained for four other isotopologues: 13 C 2 H 2 , 13 C 12 CH 2 , 13 C 12 CD 2 and 13 C 2 D 2 . The goal of the study is to spectroscopically observe and characterize vibrationally excited states from levels not significantly populated at room temperature and thus difficult to observe by normal means.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed discussion of the vibration-tovibration collisional energy transfer processes, including an energy diagram representing the vibrationally excited states more likely to be populated by these processes in the molecule of acetylene, can be found in reference. [1] The ν 2 vibration has been selected for both optical pumping and spectroscopy due to its large Raman scattering cross section. Thus, population pumping will take place through the v 2 = 1 ← v 2 = 0 transition, and the spectroscopy stage will probe for transitions that involve a change of one quantum of ν 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation